1986
DOI: 10.1056/nejm198601303140504
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response to Preexposure Human Diploid-Cell Rabies Vaccine Given Concurrently with Chloroquine

Abstract: We conducted a randomized controlled trial to evaluate the antibody response of freshman veterinary students to intradermal human diploid-cell rabies vaccine administered concurrently with chloroquine, a drug frequently used for chemoprophylaxis against malaria. Fifty-one students who had not been vaccinated against rabies were enrolled: 26 received 300 mg of chloroquine base per week (the recommended dose for malaria prophylaxis); 25 did not receive chloroquine and served as controls. All subjects received 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(25 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Individuals taking chloroquine for malaria treatment or prophylaxis may have a reduced response to ID rabies vaccination and should receive the vaccine im. [1,49,88,89].…”
Section: Id Rabies Vaccination: Challenges and Concernsmentioning
confidence: 99%
“…Individuals taking chloroquine for malaria treatment or prophylaxis may have a reduced response to ID rabies vaccination and should receive the vaccine im. [1,49,88,89].…”
Section: Id Rabies Vaccination: Challenges and Concernsmentioning
confidence: 99%
“…The safety of Pre exposure prophylaxis is firmly established. Only two documented cases of seroconversion failures have been observed among Pre exposure prophylaxis receivers especially in immuno-compromised persons (15,16 ).Chulasugandha P et al found that costs of both strategies, Pre exposure prophylaxis of children or PEP of exposed, become equal when the dog bite incidence is 2-30%; depending on which post-exposure treatment regimens (PEP) are used in study conducted in Thai children (17) The annual birth rate in Kerala is low (14.7 as per 2011 census) and the immunization coverage is high. Pre exposure prophylaxis may be implemented in a phased manner as the immunization schedule advised by WHO and IAP (18).It is also stated that the booster doses of rabies vaccines are not required for individuals living in or travelling to high risk areas who have received a complete series of pre-exposure prophylaxis with cell-culture based rabies vaccines (18,19).The Association of South East Asian Nation(ASEAN)countries adopted a call for action to prevent and control rabies with the goal of elimination by 2020.One of the ways to achieve this goal could be by pre exposure prophylaxis of all infants, children as well as on a voluntary basis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the use of CQ with pyrimethamine and sulfadoxine do not affect the immune response to oral typhoid vaccine [52]. CQ significantly reduces intradermal human diploid-cell rabies vaccine [53] and CQ prophylaxis is associated with poor antibody response to this vaccine [54]. When vaccination against rabies with this vaccine is to be used, it is recommended that the vaccine should be given before starting CQ to avoid reducing the effectiveness of the vaccine.…”
Section: Vaccinesmentioning
confidence: 99%